Developing the architecture of integrated 5G mobile network based on the adaptation of LTE technology - Tikhonov, Victor; Nesterenko, Serhii; Babich, Yurii; Таher Abdullah Qays; Berezovsky, Vasily (Eastern-European Journal of Enterprise Technologies, 2017)
The issues of constructing integrated fifth-generation mobile access networks based on the further development and modification of the LTE technology were studied. The LTE frame structure and features of using the LTE technology in real-time systems with packet delay control were analyzed. It was concluded that it is possible to reduce the time delays in the LTE radio channel by modifying the frame structure and the method of dynamic allocation of the time-frequency resource. A method was proposed for reducing delays in a radio channel by forming a dedicated logical channel in the ad hoc mode in which a channel allocation unit is formed based on the subframes. Moreover, combined synchronous and asynchronous multiplexing of real-time data into a synchronous sequence of packet transport modules was performed in the ad hoc channel. As a result of the studies, architecture and basic principles of the fifth-generation mobile access network based on modification of the LTE technology were developed. This will enable connection to the network of various sensor-equipped devices with individually specified requirements to the intensity of the data flow and allowable packet delays.